2018
DOI: 10.3390/geosciences8040116
|View full text |Cite
|
Sign up to set email alerts
|

Lithogenic and Anthropogenic Components in Surface Sediments from Lake Limboto as Shown by Magnetic Mineral Characteristics, Trace Metals, and REE Geochemistry

Abstract: Lake Limboto is one of the major lakes in Sulawesi, Indonesia. It is currently undergoing serious degradation due to population pressure. As more residential areas have been established around the lake, the sedimentation rate has increased because of the contribution of anthropogenic particles. In this study, the lithogenic and anthropogenic components in surface sediments from 17 points in the lake were studied and identified using a combination of magnetic and geochemical analyses. The results showed that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 45 publications
0
18
0
6
Order By: Relevance
“…Table 1 shows the results of magnetic susceptibility measurements in terms of χ LF (low frequency mass-specific magnetic susceptibility; measured at 470 Hz), χ HF (high frequency mass-specific magnetic susceptibility; measured at 4700 Hz), and χ FD% (frequency-dependent magnetic susceptibility; defined as 100% × (χ LF – χ HF )/χ LF ). In general, the mass-specific magnetic susceptibilities of these three river sediments are much higher than that of the surface sediments in Lake Limboto [1]. Except for that of Talumelito River, the sediments near the lake are more magnetic than that from upstream locations implying that the rivers bring more magnetic anthropogenic components to the lake.…”
Section: Datamentioning
confidence: 87%
See 1 more Smart Citation
“…Table 1 shows the results of magnetic susceptibility measurements in terms of χ LF (low frequency mass-specific magnetic susceptibility; measured at 470 Hz), χ HF (high frequency mass-specific magnetic susceptibility; measured at 4700 Hz), and χ FD% (frequency-dependent magnetic susceptibility; defined as 100% × (χ LF – χ HF )/χ LF ). In general, the mass-specific magnetic susceptibilities of these three river sediments are much higher than that of the surface sediments in Lake Limboto [1]. Except for that of Talumelito River, the sediments near the lake are more magnetic than that from upstream locations implying that the rivers bring more magnetic anthropogenic components to the lake.…”
Section: Datamentioning
confidence: 87%
“…The mineral characteristics, trace metals, REE geochemistry of surface sediments in Lake Limboto has been reported elsewhere [1]. The properties have been widely used, among others, to distinguish anthropogenic components from the lithogenic components in lake [1], [2], [3], [4], [5], [6] as well in suspended river sediments [7], [8], [9], [10].
Fig. 1Locations of sampling points (black triangles) along Alopohu (Alo01 and Alo02), Bionga (Bionga01 and Bionga02), and Talumelito (Talumelito01 and Talumelito02) rivers that serve as inlets to Lake Limboto.
…”
Section: Datamentioning
confidence: 99%
“…Table 1 shows magnetic susceptibility measurement data on Brantas river bulk surface sediment samples. Several other studies have shown that magnetic susceptibility measurement was not only conducted on sediments from rivers [3], [4] but also on sediments from coasts [5], [6] and lakes [7], [8] and other materials such as mineral deposit [9] and guano [10], [11]. Previous studies have shown that frequency-dependent magnetic susceptibility was used to determine superparamagnetic grain content in sediments [12], [13].…”
Section: Datamentioning
confidence: 99%
“…Cluster analysis shows that this group is most represented by SIRM (Supplementary Table S1). The magnetic parameters reflect a mixture of anthropogenic and geogenic inputs, however, the lack of statistical correlation observed between the magnetic parameters and Fe ( Supplementary Table S2), indicates an overriding anthropogenic magnetic signal (Yunginger et al, 2018). Some Ca is likely to derive from the surrounding limestone (CaCO 3 ) geology; however, the loading of Ca on PC2 instead of the minerogenic PC1 and strong correlations with SIRM, SOFT 20 , and χ LF , highlight an anthropogenic source.…”
Section: Anthropogenic Signals In Skpmentioning
confidence: 99%